Analysis of the productive dynamics of corn (Zea mays L.) in the municipality of Cabaceiras, Paraíba, from 2004 to 2023 - Muniz, Janaina Iris de Azevedo Silva; Albuquerque Jr., Aldo Muniz de; Andrade, Wellerson; Sousa, Hemily Hemily Tainá Gouveia de; Bezerra, Byanca de Fátima Gomes; Marques, Maria Andrielly Gomes; Nascimento, Paulo Ricardo Ferreira do; Sousa, Francisco de Assys Romero da Mota; Barbosa Jr., Afonso; Isidro, Renato; Barbosa, Maykon Douglas Gomes; Abreu, Khyson Gomes; et al. (Brazilian Journal of Production Engineering, 2026)
This study analyzed the productive dynamics of maize (Zea mays L.) in the municipality of Cabaceiras, Paraíba, from 2004 to 2023, using data from the Municipal Agricultural Production of the Brazilian Institute of Geography and Statistics. Five variables were evaluated: planted area, harvested area, quantity produced, average yield, and value of production. The data were graphically organized and analyzed using Principal Component Analysis with the R software. The results showed high interannual variability in all variables, reflecting the instability characteristic of rainfall-dependent agricultural systems in the Semi-arid region. An alternation was observed between years of expansion of cultivated area and production and periods of strong contraction or absence of cultivation, indicating high sensitivity of the crop to climatic conditions and local technological limitations. In years with better rainfall conditions, peaks in planted area, production, and economic value occurred, while several years registered low production levels or absence of harvest. Multivariate analysis indicated a strong association between quantity produced, average yield, and production value, highlighting the importance of productivity for the economic performance of the crop. The results reinforce the need for adaptive strategies that promote greater productive stability and sustainability of agriculture in the Semi-arid region.
Keywords: Data analysis; family farming; public policies; production technologies